Analysis of Besaman Music Rhythm Patterns - Hardiansyah Ay (Institut Seni Indonesia Denpasar, 2020)
Besaman (bersaman) is a daily mention of the Gayo people for art activities which are currently only known as saman dance. saman is a traditional Gayo art which includes music, dance and literature. Within the elements of music, dance and literature have an equally important portion, in which each type of art takes place in mutualism, such as the motion of creating music, music (melodic form of song and poetic structure) is considered in creating the rhythm of motion. In the perspective of dance music, saman is a dance that uses a form of music presentation internally, internally what is meant is music that arises or is produced by the dancer itself (without accompaniment of music). Music in besaman is produced by clapping hands, chest, thighs, finger flicks and vocals. Clapping hands, chest, thighs and flick fingers form a choreography in the dance. The forms of song melodies and literary structures adjust and are also adjusted in creating a form of musical rhythm as well as dance moves. Therefore, the Gayo community calls this form of art activity with the plait not just dancing saman, because the three types of music, dance and literature take an equally important role in doing this art.